(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the frailty in elderly people undergoing hip arthroplasty at the Anesthesia and Resuscitation Center, Bach Mai Hospital. Method: A cross-sectional descriptive research was performed. A total of 104 elderly patients were invited to the study who were scheduled for hip arthroplasty at the Anesthesia and Resuscitation Center of Bach Mai Hospital from October 2022 to August 2023. Preoperative Frailty index evaluated. Clinical and paraclinical information was also collected. Results: The proportion of patients with frailty (frailty index ≥ 0.25) in this study was 36.5%. The proportion of patients with frailty was significantly higher in the group > 80 years old (61.8%), women (44.6%), with unintentional weight loss (73.3%), and with 3 or more comorbidities (67.9%), limited daily activities or dependence diagnosed with impairment (50.0%), and dependence when exercising/moving before the fracture (54.4%). Patients with ASA III/IV classification were diagnosed with frailty (61.5%) at a significantly higher rate than patients with ASA II classification (21.5%) with p<0.001. Conclusion: The rate of frailty in elderly people undergoing hip surgery was high. Older age, female gender, unintentional weight loss, limited daily activities and multi-morbidities were important factors associated with frailty in this patient group.